2015
DOI: 10.1186/s12864-015-2289-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the genomic traits of fungus-feeding bacterial genus Collimonas

Abstract: BackgroundCollimonas is a genus belonging to the class of Betaproteobacteria and consists mostly of soil bacteria with the ability to exploit living fungi as food source (mycophagy). Collimonas strains differ in a range of activities, including swimming motility, quorum sensing, extracellular protease activity, siderophore production, and antimicrobial activities.ResultsIn order to reveal ecological traits possibly related to Collimonas lifestyle and secondary metabolites production, we performed a comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 97 publications
(104 reference statements)
5
66
0
Order By: Relevance
“…gpAD87_25000, gpAD87_13180, bAD24_II11090, bAD24_p01610. Despite the advantages made in the field of genome sequencing and genome annotation a vast percentage of bacterial genome sequences remains with unknown function (Galperin and Koonin, 2004;Song et al, 2015). Independent studies also indicated that such "unknown genes" are differentially expressed during interspecific interactions between bacteria (Garbeva et al, 2011b;Garbeva et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…gpAD87_25000, gpAD87_13180, bAD24_II11090, bAD24_p01610. Despite the advantages made in the field of genome sequencing and genome annotation a vast percentage of bacterial genome sequences remains with unknown function (Galperin and Koonin, 2004;Song et al, 2015). Independent studies also indicated that such "unknown genes" are differentially expressed during interspecific interactions between bacteria (Garbeva et al, 2011b;Garbeva et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…By testing various volatile-mediated interactions between phylogenetically different soil bacteria and protists and comparing those with direct trophic interactions, they demonstrated that specific bacterial volatiles can provide early information about suitable prey. In particular, it was shown that terpenes such as β-Linalool, β-Pinene, Germacrene D-4-ol or δ-Cadinene produced by C. pratensis Ter91 (Song et al 2015b) can stimulate protist activity and motility suggesting that terpenes can be key components in VOCs-mediated communication between protists and bacteria (Schulz-Bohm et al 2017a). Interestingly, soil protists such as Dictyostelium discoideum ) produce volatile terpenes.…”
Section: Protists-bacteriamentioning
confidence: 99%
“…This has revealed that, without physical contact, microorganisms are able to drastically alter plant root system development, plant physiology, hormonal pathways, and biomass production (Ryu et al 2004;Blom et al 2011;Wenke et al 2012;Bailly et al 2014;Bitas et al 2015;Ditengou et al 2015;Piechulla et al 2017). mVOCs can also function as a direct source of nutrients for plants (Meldau et al 2013), induce resistance to pathogens in plants (D'Alessandro et al 2014;Kottb et al 2015;Song et al 2015b;Wintermans et al 2016), affect plant secondary metabolite production (Santoro et al 2011), directly inhibit plant pathogens Garbeva et al 2014b;De Vrieze et al 2015;Kottb et al 2015) and induce soil fungistasis and suppressiveness (Garbeva et al 2011a;Van Agtmaal et al 201). Moreover, one single mVOC can show various functions, such as dimethyl disulfide, which improves plant growth by enhancing the availability of reduced sulfur (Meldau et al 2013).…”
Section: Vocs In Microbe-plant Interactionsmentioning
confidence: 99%
See 2 more Smart Citations